(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the status of fana in the work of Hazrat Alisher Navoi “Nasaimu-l-Mukhabbat”, the theoretical views of mystics regarding its essence, as well as the artistic interpretation of this status.